Lactobacillus salivarius metabolite succinate enhances chicken intestinal stem cell activities via the SUCNR1-mitochondria axis - Danni Luo; Minyao Zou; Xi Rao; Mingping Wei; Lingzhi Zhang; Yuping Hua; Lingzi Yu; Jiajia Cao; Jinyi Ye; Sichao Qi; Huanan Wang; Yuling Mi; et al. (Poultry Science)
The activity of intestinal stem cells (ISCs) can be modulated by Lactobacillus, which subsequently affects the mucosal absorptive capacity. However, the underlying mechanisms remain unclear. In this study, a total of 189 Hy-Line Brown chickens (Gallus) were randomly assigned to one of seven experimental groups (n = 27 per group). These groups included a control group, a vehicle group (MRS group), a Lactobacillus salivarius group, a L. salivarius supernatant group, and three succinate treatment groups with various dosages. Each group was further subdivided into three replicates, with 9 chickens per replicate. The results indicate that the administration of Lactobacillus salivarius supernatant to laying hens notably increased the mRNA abundance of the amino acid transporters oligopeptide transporter 1 (PepT1) and sodium-dependent neutral amino acid transporter (B0AT). Metabolomic analyses indicated that the supernatant contains a high concentration of organic acids. Among them, succinate could enhance mRNA abundance of PepT1, B0AT and excitatory amino acid transporters 3 (EAAT3) both in vivo and in vitro. Accordingly, succinate could accelerate intestinal epithelial turnover, as indicated by the increased levels of cyclin-dependent kinase 2 (Cdk2) mRNA and proliferating cell nuclear antigen protein (PCNA), as well as ISC differentiation-related protein leucine-rich repeat containing G protein-coupled receptor 5 (LGR5). Furthermore, succinate treatment was shown to elevate the levels of mitochondrial fusion proteins optic atrophy 1 (OPA1) and translocase of outer mitochondrial membrane 20 (TOMM20), resulting in increased local ATP levels. However, pretreatment with NF-56-EJ40, a succinate receptor antagonist, attenuated the effects of succinate on OPA1, TOMM20, and ATP levels, alone with the reducing LGR5 and PCNA levels. Collectively, succinate, a metabolite of L. salivarius, activates the SUCNR1-mitochondria axis in ISCs, facilitating mitochondrial ATP synthesis, promoting ISC activity, and ultimately enhancing mucosal absorptive capacity.